Respostas

2013-12-18T18:54:20-02:00
Faça as identidades: sen(a+b) = sen(a)cos(b) + cos(a)sen(b)
                               cos(a-b) = cos(a)cos(b) + sen(a)sen(b)
                               tg(a+b) = sen(a+b)/cos(a+b)
                               cos²(x) = 1 - sen²(x)
                               então cos²(a) = 1 - 16/25 = 0,36 e cos(a) = 0,6
                               então cos²(b) = 1 - 144/169 = 0,148 e cos(b) = 0,385
                                substituindo sen(a+b) = 0,308 + 0,554 = 0,862
                               cos(a-b) = 0,97 e cos(a+b) = -0,51
e finalmente a tg(a+b) = -1,7   (valor com arredondamento)
2 2 2